Peer support after clinical incidents in veterinary care: Adopting the RISE (Resilience In Stressful Events) program - Lisen Schortz; Liz Mossop; Catherine Oxtoby; Annika Bergström; Albert W. Wu (PLoS ONE, 2026)
Veterinary professionals often experience emotional distress after clinical incidents, affecting well-being and job performance. This study explores the adaptation and implementation of the Resilience In Stressful Events (RISE) program, originally developed for human healthcare, to support veterinary clinicians. RISE provides peer support through trained responders, focusing on emotional care rather than event details. Findings indicate that the RISE program is both acceptable and feasible for veterinary settings, with minor adaptations, such as including veterinary examples, to fit veterinary specific needs. The study highlights the importance of structured support systems in improving the mental health and retention of veterinary professionals, suggesting that programs like RISE could play a crucial role in enhancing clinician wellbeing and care quality.